2014
DOI: 10.1371/journal.pone.0092787
|View full text |Cite
|
Sign up to set email alerts
|

Black Tattoos Entail Substantial Uptake of Genotoxicpolycyclic Aromatic Hydrocarbons (PAH) in Human Skin and Regional Lymph Nodes

Abstract: Hundreds of millions of people worldwide have tattoos, which predominantly contain black inks consisting of soot products like Carbon Black or polycyclic aromatic hydrocarbons (PAH). We recently found up to 200 μg/g of PAH in commercial black inks. After skin tattooing, a substantial part of the ink and PAH should be transported to other anatomical sites like the regional lymph nodes. To allow a first estimation of health risk, we aimed to extract and quantify the amount of PAH in black tattooed skin and the r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 38 publications
1
29
0
10
Order By: Relevance
“…By light microscopy we observed large aggregates of pigment in the skin and lymph nodes in accordance with the literature [6][7][8][9]21] . Light microscopy includes a much larger tissue sample and section thickness but this method is limited by inadequate resolution and only allows larger aggregates of pigments to be visualized.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…By light microscopy we observed large aggregates of pigment in the skin and lymph nodes in accordance with the literature [6][7][8][9]21] . Light microscopy includes a much larger tissue sample and section thickness but this method is limited by inadequate resolution and only allows larger aggregates of pigments to be visualized.…”
Section: Discussionsupporting
confidence: 91%
“…A study of human skin tattooed black and the regional lymph nodes confirmed that black pigment and polyaromatic hydrocarbons were found in the lymph nodes in high amounts [21] . Deposition of tattoo pigment in the skin is not stationary.…”
Section: Discussionmentioning
confidence: 87%
“…A tattoo is essentially one large single exposure. PAHs escape to the lymph and directly to the blood stream . Metabolism of PAHs occurs primarily by enzymatic processes and via oxidation by cytochrome P450 in the liver .…”
Section: Discussionmentioning
confidence: 99%
“…Yet, the lymphatic system seems to play a major role in the transport of the applied pigments and its impurities. Black ink could be extracted and analyzed from skin and regional lymph nodes (Lehner et al 2014). Possibly adsorbed to carbon black, polycyclic aromatic hydrocarbons (PAHs) could be simultaneously detected in concentrations reaching 0.6 μg/ cm 2 in the skin samples and 11.8 μg/g in the lymph nodes, respectively.…”
Section: Biodistribution Of Tattoo Inks: In Vivo and Ex Vivo Evidencementioning
confidence: 99%